MODEL PEMBELAJARAN DILI (DISCOVERY LEARNING DAN INQUIRY) DALAM MENINGKATKAN HASIL BELAJAR SISWA SMA NEGERI 7 AMBON - Mariske Kewere; M Nur Matdoan; Ine Airini (BIOPENDIX, 2019)
Background: In achieving a learning goal a teacher is required to be able to choose an effective learning model to be applied in a particular concept. One of the causes of students' lack of understanding of a concept is teacher-centered learning and lack of motivation in students in the learning process. The Discovery Learning and Inquiry learning model is a series of learning activities that maximally involve all students' abilities to search and investigate systematically, critically, logically, analytically, so that they are able to solve the problems themselves with confidence. Method: This study uses the Discovery Learning and Inquiry learning model on the concept of viruses in class X2 of SMA Negeri 7 Ambon. This research was conducted from 16 February to 16 March 2019. Results: This study shows that there is an increase in student learning outcomes after using the Discovery Learning learning model that is integrated with the Inquiry model. Conclusion: From the learning outcomes that are based on the student's final grade shows that there is an increase in the initial test results of students who have not reached the minimum completeness criteria and the final test has reached the minimum completeness criteria (KKM).